UTILIZATION OF LEARNING MEDIA ON STUDENT MOTIVATION At AN-NAFIS KINDERGARTEN TELUK MENGKUDU - Septi Ayu Syahraini; Nurazizah Sitorus; Rana Manik; Cindy Cindy; Siti Salimah Nasution; Siti Aisyah (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of using media on children's learning motivation is to provide a real picture of new information and ideas and without material that the teacher will convey to the knowledge that will be given to children, so that understanding from the teacher becomes easier. The media used cannot be separated from materials that are safe, harmless and easy to use so that children can explore these media to add to the child's learning experience. The type of learning media used is physical, in addition to media numbers cards, among smart trees, and many others, used materials that are safe, easy to obtain and harmless, so that children can easily explore them to explore curiosity and can find out various things. . The results of the use of this learning media can bring up children's learning motivation. This can be seen from the children's interest in seeing and listening to the teacher who tells stories using the media. Children can express their ideas, the results of observations in the environment around them and their experiences. So that the meaning of learning and understanding of the material obtained by the child and the material presented by the teacher is in the same direction.